Innovation in Small-Scale Retailing: A Future Research Agenda. (May 2013) - Quinn, Barry; McKitterick, Lynsey; McAdam, Rodney; Brennan, Michael
For small retailers facing significant challenges it can be argued that, in light of their restricted resources, innovation is critical for business development and competitive advantage. However, there has been a lack of research into the potential for innovation in small retailing and the types of innovative activity that can be applied. This conceptual paper uses key themes from various literature bases, including small retailing, small business innovation, services and retail innovation, to provide a future research agenda for small retailer innovation.